ANALISIS MANAJEMEN KONTRUKSI PROYEK PEMBANGUNAN GEDUNG PASCASARJANA UNIVERSITAS PENDIDIKAN INDONESIA (UPI) BANDUNG - Gunawan, Andi; Farhan, Ohan; Rohman, Fathur (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
Construction management is an effort to use limited resources efficiently, effectively and on time in completing a predetermined / planned project. There are 3 activities from the basic functions of project management, namely planning, implementing and controlling. Of the three activities, control is carried out on resources in a project which includes manpower, equipment (machine), materials (material), money (money) and methods (methods). The research aims to analyze the construction management of the construction project of the postgraduate building of the Indonesian University of Education (UPI) Bandung, planning the cost budget and scheduling using the Barchart, S Curve and Critical Path Method (CPM) methods. The results of this study show that the Budget Plan (RAB) obtained for the Postgraduate Building Construction Project of the University of Education of Indosesia (UPI) Bandung amounted to Rp 45,416,418,967, then the results of scheduling using barcharts and the S curve that this project took 32 weeks to complete the structural work, while the results of the Critical Path Method (CPM) analysis to complete this project took 224 days. Keyword: Construction Management, Cost Budget Plan, S Curve, Critical Path Method.